Leveraging Technology to Improve Business during and after the Pandemic - Wouroud ElFarmawi (Garuda Prestasi Nusantara Consulting, 2023)
The entire world came to a halt in 2020 because of Covid 19 pandemic. Businesses were closed and people from all over the world were quarantined. Some businesses, however, were able to continue operations through an existing pickup online program. Businesses that closed or were fearful of reopening may find that shifting to online marketing is the best solution. Understanding the significance of transitioning businesses from a physical location to an online one is an important goal to strive for. There are numerous short- and long-term benefits to moving businesses online through. Businesses can improve process efficiency, performance, and productivity by leveraging technological tools such as project management software (PMS), customer relationship management (CRM), task management tools (TMT), email marketing, Salesforce, and others. This article investigated how small businesses in the United States (US) benefited from technological tools and added value through their performance during the pandemic. It also aimed to educate business owners who still do not believe that technology can be used to automate their operations for effective performance and long-term customer relationships. The article seeks to encourage small-business owners to use their talents, competencies, and technology tools for the betterment of their organizations. Keywords: Technological Tools, Business Processes, COVID-19 pandemic, E-commerce